(untitled) (Research, Society and Development, 2021)
Objective: This article aims to verify whether the use of cyanoacrylate glue in surgical procedures produces beneficial outcomes for the patient regarding healing and cost benefit. Methods: An integrative literature review was performed in the PubMed, Bireme/BVS and SciELO databases, including articles referring to cyanoacrylates, surgeries and sutures in humans, published in Portuguese, English and Spanish. Literature review articles, dissertations, book chapters, case studies, and editorials were excluded. Results: A total of 897 articles were found, of which 830 were excluded after applying the inclusion and exclusion criteria, and after reading the abstracts and full texts. Thus, 67 articles were included in this review. Conclusion: Studies have shown that cyanoacrylate glues can be used as an alternative in surgical procedures, mainly due to their ease of application, decreased risk of contamination and increased healing efficiency. Although they do not replace sutures in all surgical procedures, cyanoacrylate glues are a fast, inexpensive and cost-effective method of healing, specifically in plastic, ophthalmic and cardiac surgeries.